Multilingualism and Englishization in international business communication: the case of some Italian wine producers: Is English going to be supplanted as the language of international business?. Issue 1 (10th December 2015) - Pierini, Francesco
Abstract : It goes without saying that a common culture and a common language make trade easier between individuals and countries, and for this reason the human being has always tried to find a way to communicate with foreign people in order to buy and sell goods and services. But learning as many languages as the market requires has always been a rather difficult issue, so since ancient times some languages have played the role of lingua franca . Throughout history there have been various lingua francas in the world, used as working languages or bridge languages, based on the prestige and economic relevance of some countries in particular phases of history, as is the case with Latin in the Roman Empire; in the Eastern provinces of the Empire Greek served the same purpose (De Houwer & Wilton, 2011).